Kristen Progresif Sebagai Inflitrasi Gerakan Zaman Baru ke dalam Gereja Kontemporer - Laurentia Donna Maria; Setyobekti, Andreas Budi (Sekolah Tinggi Teologi Baptis Indonesia, 2024)
The emergence of the Progressive Christian sect in Indonesia, initiated by Tiktoker Brian Siawarta through various video uploads both on his Tiktok and Instagram social media, has caused a disruption among the church. This is mainly because of his teaching which states that there is salvation outside the Lord Jesus, one of which is through good deeds or loving your neighbour. Previous researcher, Royke Lantupa Kumowal, studied this sect as a form of universalist gnosticism because they positioned themselves as having secret knowledge or revelations that were not revealed to other Christians. Another writer, Kevin Nobel, highlights the nuances of liberal theology in this sect which he draws far back, namely since the sexual revolution period in the 1960s. This research uses a literature study method to compare the main components of the New Age Movement (NAM) with Progressive Christian teachings. The research results show that there are significant similarities between the two in the aspects of pantheism, reincarnation, relativism and esotericism. In conclusion, the Progressive Christian sect can be seen as a form of NAM’s infiltration into the church by using Christian terminology that seeks to match the identity and language of Christians in order to